1998
DOI: 10.1002/(sici)1097-0215(19980504)76:3<325::aid-ijc7>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic risks of endometrial carcinoma after treatment for breast cancer in a large French case-control study

Abstract: Since tamoxifen is widely used in breast cancer treatment and has been proposed for the prevention of breast cancer, its endometrial iatrogenic effects must be carefully examined. We have investigated the association between endometrial cancer and tamoxifen use or other treatments in women treated for breast cancer in a case‐control study. Cases of endometrial cancer diagnosed after breast cancer (n = 135) and 467 controls matched for age, year of diagnosis of breast cancer and hospital and survival time with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 20 publications
3
40
0
8
Order By: Relevance
“…In larger epidemiological studies, the relative risk of endometrial carcinoma is estimated to be two to threefold, the risk increasing with the duration and the cumulative dose of tamoxifen treatment. [2][3][4][5][6][7] In postmenopausal women tamoxifen exerts a proliferative effect on the endometrium, as measured by the hyperdiploid fraction, 8 and clinical studies have reported an increased incidence of endometrial polyps and hyperplastic endometrial changes, mostly interpreted as evidence of the agonistic effect of tamoxifen. [9][10][11][12][13][14] Histology of tamoxifen exposed postmenopausal endometrium in general shows a characteristic picture of a condensated, hypercellular, collagen rich stroma, whereas the glandular epithelium stays thin and atrophic or metaplastic, the flattened epithelium lining cystically dilated glands or polyps.…”
mentioning
confidence: 99%
“…In larger epidemiological studies, the relative risk of endometrial carcinoma is estimated to be two to threefold, the risk increasing with the duration and the cumulative dose of tamoxifen treatment. [2][3][4][5][6][7] In postmenopausal women tamoxifen exerts a proliferative effect on the endometrium, as measured by the hyperdiploid fraction, 8 and clinical studies have reported an increased incidence of endometrial polyps and hyperplastic endometrial changes, mostly interpreted as evidence of the agonistic effect of tamoxifen. [9][10][11][12][13][14] Histology of tamoxifen exposed postmenopausal endometrium in general shows a characteristic picture of a condensated, hypercellular, collagen rich stroma, whereas the glandular epithelium stays thin and atrophic or metaplastic, the flattened epithelium lining cystically dilated glands or polyps.…”
mentioning
confidence: 99%
“…No obstante no se aconseja su uso durante más de cinco años por el riesgo de cáncer sobre el endometrio 6 . La patología endometrial es más frecuente en mujeres con cáncer de mama tratadas con tamoxifeno que en las no tratadas 7 , existen múltiples publicaciones que demuestran un incremento del riesgo relativo del cáncer endometrial en mujeres con cáncer de mama tratadas con tamoxifeno versus las no tratadas [7][8][9][10][11] , Odds Ratio (OR) = 2.4, 95% Intervalo de Confianza (CI) = 1.8-3.0 e íntimamente relacionado con la duración del tratamiento; si comparamos tratadas más de 5 años con no tratadas el riesgo aumenta OR = 3.6 95% CI = 2.6-4.8.…”
Section: Discussionunclassified
“…9 12 . La mayoría de los carcinomas diagnosticados son endometrioides o adenocarcinomas como ocurre en nuestra serie 9,13 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The risk of developing endometrial cancer in patients treated with tamoxifen is dose and duration dependent [26][27][28][29][30].…”
Section: The Impact Of Duration Of Tamoxifen Treatmentmentioning
confidence: 99%